The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1123/jpah.2020-0526
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Prevalence of Physical Activity, and Barriers and Facilitators to Physical Activity, in Informal Carers in the United Kingdom

Abstract: Background: It is estimated that 17% of the UK adult population are informal carers, usually for a family member, with a majority reporting that they are not able to engage in physical activity as much as they would like. The aim of this review is to provide a greater understanding of the prevalence of, and barriers and facilitators to, physical activity of informal carers in the United Kingdom. Methods: A systematic review of relevant databases and grey literature was undertaken, following Preferred Reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…YACs reported being less physically active than students without care responsibilities. According to a systematic review on physical activity in informal carers, across age groups, informal carers place their own health needs as secondary to the health of the care-recipient [ 36 ]. Even though the number of studies examining physical activities among informal carers is very scarce, it was concluded that the level of physical activity among informal carers is below what they themselves desire, below governmental guidelines and below what is commonly found in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…YACs reported being less physically active than students without care responsibilities. According to a systematic review on physical activity in informal carers, across age groups, informal carers place their own health needs as secondary to the health of the care-recipient [ 36 ]. Even though the number of studies examining physical activities among informal carers is very scarce, it was concluded that the level of physical activity among informal carers is below what they themselves desire, below governmental guidelines and below what is commonly found in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…33 It was noted in this study that no known SR had been conducted on studies exploring the current (i.e., during the COVID-19 pandemic) facilitators and barriers to PA among (UK)-based adults. 20,21,28 The recent SRs (2016 till date) on the facilitators and barriers of PA among (UK)-based adults were based on studies that were conducted before the COVID-19 pandemic 20,21,28 ; hence, they may not be up to date with the current challenges in the (UK) The COVID-19 pandemic has brought significant changes to people's lifestyles, including PA. 18,19 This change has modified the facilitators and barriers of PA among (UK)-based adults. 18,19 Hence, there is a need for a SR of current primary studies (conducted from 2020 till date) exploring the facilitators and barriers to PA among (UK)-based adults.…”
Section: Discussionmentioning
confidence: 99%
“…20,21,28 At the interpersonal level, "having the opportunity for PArelated support and social interaction/participation" was a facilitator reported by all the included SRs. 20,21,28 At the environmental level, no facilitator was commonly reported in all the included SRs. However, only two SRs reported "having a safe environment for PA" as a facilitator to PA. 20,21 Barriers to PA ►Table 6 shows the full list of the synthesized barriers (a thematic area) to PA from the included SRs.…”
Section: Facilitators To Pamentioning
confidence: 99%
See 2 more Smart Citations